Pictorial essay: Neuroimaging of stroke - Hassan, Radhiana; ahmad mukari, shahizon; syed osman, syazarina; hashim, hilwati; mohd zain, norzaini rose; Muda, Ahmad Sobri (2012)
Evaluation of early stroke is one of the most common radiological procedures requested. This pictorial essay illustrates on the basic neuroimaging findings of ischemic stroke. The early signs of ischemia including loss of the insular ribbon sign, hyperdense middle cerebral artery and focal loss of grey white matter differentiation on computed tomography (CT) and localization of stroke using diffusion- weighted MR sequences will be presented. It will expose the clinician through the spectrum of imaging findings of ischemic stroke. Integration of MRI, vascular and perfusion imaging is given in different clinical scenarios